The Influence of Repetition of Reading and Rewards on Memorizing the Qur'an in 14-Year-Old Children: - - Fitri Kurnia Sari Sari (Institut Agama Islam Sumatera Barat Pariaman, 2025)
The ability to memorize the Quran is an important competency in Islamic religious education, especially for adolescents who are in the optimal cognitive development phase. In reality, not all children have the same ability to retain their memorization. This condition indicates the need for effective learning strategies. Repetition of reading is a basic technique believed to strengthen long-term memory. Meanwhile, rewards act as positive reinforcement that can increase motivation, focus, and enthusiasm for children in memorizing. The method used was a single-subject experimental design with a pre-test design, intervention with 10 repetitions of reading, reward administration, and post-test. Data analysis used visual graphic techniques (line graphs) to show changes in memorization results from the pre-test, intervention, and post-test phases. The results showed a significant increase in the number of verses memorized and memorization accuracy after the intervention of a combination of repetition of reading and rewards. Repetition of reading and rewards is very effective in improving Quran memorization ability in 14-year-old children. The intervention's effects were seen in improved scores across all assessment aspects: fluency, tajweed accuracy, verse sequence, and duration. Rewards provided additional motivation, helping subjects focus and maintain their memorization..